The Westing game - Raskin, Ellen (New York, N.Y. : Puffin, 1992)
The mysterious death of an eccentric millionaire brings together an unlikely assortment of heirs who must uncover the circumstances of his death before they can claim their inheritance.
"Winner of the Newbery Medal"--Cover.
4-6
5-8
Keywords: Inheritance and succession -- Fiction; Mystery and detective stories; Inheritance and succession -- Fiction; Mystery fiction